Analisis Penyusunan Rencana Pelaksanaan Pembelajaran dalam Kurikulum 2013 - Isro Royhanna; Rafiqah Alya; Gusmaneli Gusmaneli (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Making lesson plans (RPPs) is an essential part of implementing the 2013 curriculum because it gives instructors a practical guidance for carrying out the learning process, which is focused on developing students' character and taking a scientific approach. The purpose of this study is to evaluate the appropriateness and quality of the RPP that instructors created in relation to the 2013 Curriculum. The RPP was created by teachers in several elementary and high schools using a document study approach and a descriptive qualitative research methodology. According to Permendikbud Number 14 of 2019, the majority of RPPs have incorporated the required elements, including subject identity, core and basic competencies, learning objectives, learning materials, methods, media, learning resources, learning steps, and assessment. Authentic evaluation, literacy integration, and the application of a thorough scientific approach were nevertheless determined to have shortcomings and were not yet at their best. These results show that in order to increase the quality of learning planning in accordance with the 2013 Curriculum's tenets, teachers' capability must be strengthened through ongoing training and professional development.